The Role of the Family in Early Childhood Moral Education: The Perspective of Al-Ghazali, Ibn Sina, Abdullah Nasih Ulwan - Mushoffatin Ni’mah; Nita Yuli Astuti (Yayasan Pendidikan Haiba Nasywa in cooperation with Pesantren Wahdatul Ulum Internasional, 2025)
Abstract This research aims to explore the role of the family in early childhood moral education from an Islamic perspective, focusing on the views of Imam Al-Ghazali, Ibn Sina, and Abdullah Nasih Ulwan. The research method used is a qualitative literature review, referring to classic books such as Ihya Ulumuddin and various modern sources related to moral education. The results show that the family has a central role as the main agent in instilling moral values through modeling, habituation, and teaching Qur'anic values from an early age. Moral education not only covers moral aspects but also equips children with practical skills to become productive members of society. This research emphasizes the importance of methods such as tadarrus, Islamic stories and daily prayers in building a child's spiritual and intellectual foundation. With the implementation of appropriate strategies, families can strengthen their function as primary educators in a modern era filled with the challenges of globalization and technological advancement. The findings provide practical insights for parents and educators to educate children holistically to grow into individuals who are civilized, have integrity, and are beneficial to humanity. Keywords: Moral Education, Family, Early Childhood.